Expression and clinical significance of the NEK7-NLRP3 inflammasome signaling pathway in patients with systemic lupus erythematosus - Zhen-Zhen Ma; Hong-Sheng Sun; Ji-Cai Lv; Lei Guo; Qing-Rui Yang (BMC, 2018)
Abstract Background The aim of the study was to investigate the expression of the NEK7-NLRP3 inflammasome signaling pathway in the peripheral blood mononuclear cells (PBMCs) of patients with systemic lupus erythematosus (SLE), as well as its clinical significance. Methods A total of 38 SLE patients and 33 healthy volunteers were recruited. Real time PCR and western blotting were performed to determine mRNA and protein levels of NEK7, NLRP3 inflammasome components (NLRP3, ASC, and Caspase-1), and downstream cytokines (IL-1b and IL-18) in PBMCs from the two groups. ELISA was used to detect serum levels of IL-1b and IL-18. The same methods were used to detect changes in the above indices in the 25 SLE patients after treatment. Correlations between clinical and laboratory parameters were also analyzed. Results Compared to those in healthy controls, levels of NEK7, NLPR3, and ASC were lower in SLE patients; however, Caspase-1, IL-1b, and IL-18 were expressed at higher levels. mRNA levels of NEK7, NLRP3, and ASC were inversely correlated with disease activity, whereas a positive correlation was observed with IL-1b and IL-18. After treatment, mRNA levels of NEK7 and NLRP3 increased, whereas Caspase-1, IL-1b, and IL-18 decreased significantly. Compared to those in SLE patients without renal damage, patients with lupus nephritis (LN) exhibited lower mRNA levels of NEK7, NLRP3, and ASC but higher levels of Caspase-1, IL-1b, and IL-18. Conclusions Results indicate that the expression of the NEK7-NLRP3 complex might play a protective role in the pathogenesis of SLE and is inversely correlated with disease activity. A positive effect of NEK7 on NLRP3 was observed, and the low expression of NLRP3 in SLE patients might be related to the low expression of NEK7. Overexpression of Caspase-1 in SLE patients mediates the maturation and release of IL-1b and IL-18, and contributes to the pathogenesis of SLE and LN.